Does robotic distal pancreatectomy surgery offer similar results as laparoscopic and open approach? A comparative study from a single medical center. Issue 3 (16th January 2014) - Duran, Hipolito; Ielpo, Benedetto; Caruso, Riccardo; Ferri, Valentina; Quijano, Yolanda; Diaz, Eduardo; Fabra, Isabel; Oliva, Catalina; Olivares, Sergio; Vicente, Emilio
Abstract Introduction In the field of pancreatic surgery, robotic surgery has yet to be evaluated against open and laparoscopic approaches. The outcomes of robotic surgery for distal pancreatectomy were analysed and the results compared with those of laparoscopic and open procedures. Methods Retrospective reviews were made of 47 patients who underwent distal pancreatectomy at our institution between 2008 and 2013 with three different approaches: 16 robotic, 18 laparoscopic and 13 open surgeries. Results A significant difference was observed in blood loss in the open group (mean 3.44 units) compared with the robotic (mean 0.5 units) and laparoscopic (0 units) technique (P = 0.046). A shorter hospital stay was observed for the robotic group (8.87 days) compared with the laparoscopic (19.16 days) and open groups (20.44 days) (P = 0.035). Morbidity was lower in the robotic group (0%) compared with the Laparoscopic (44%) and Open groups (46%) (P = 0.014). Conclusions These findings support the proposition that robotic distal pancreatectomy is as safe as the laparoscopic approach. Copyright © 2014 John Wiley & Sons, Ltd.